STATUS REFINEMENT OF METAL-POOR STAR HD 6268 - Mishenina, T.; Usenko, I.; Kniazev, A.; Kovtyukh, V. (Одеські астрономічні публікації, 2018)
Metal-poor stars in the Galaxy enable observations of the light and neutron-capture (n-capture) elements produced by their progenitors and deduction of the characteristics of the early Galaxy from the elemental abundances in these stars. Stars with deficiency of metals ([Fe/H] < –2) vary significantly in their chemical composition, in particular, in their content of CNO elements, as well as the iron-peak and n-capture elements. A detailed study of the elemental abundances in these stars makes it possible to test experimental models of stellar evolution, nucleosynthesis, homogeneity (the degree of mixing) of interstellar matter, etc., at low metallicity in the Galaxy. The metal-poor star HD 6268 with [Fe/H] close to –2.5 and low carbon abundance was selected as a target one for this study. The spectral material was collected using the Southern African Large Telescope (SALT) fibre-fed echelle-spectrograph HRS in the medium resolution mode (R 31000-41000) with a high S/N ratio near 100-200 within the range from 3900 to 8700 ÅÅ. The atmospheric stellar parameters and abundances of 30 chemical elements in the metal-poor star HD 6268 were determined under the LTE approximation using the atmosphere models by Kurucz & Castelli (2003), as well as the equivalent widths EWs and WIDH9 code developed by Kurucz. The abundances of C, Na, Mg, K, Ba, La, Ce, Pr, Sm and Eu were obtained by the synthetic spectrum method factoring in the hyperfine structure (HFS) for the Eu II line4129 A. The carbon abundance was determined by the molecular synthesis fitting in the region of CH (4300-4330 ÅÅ). For the abundances of Na, Mg, K and Ba, we applied the NLTE corrections. As a result, we found out that the abundances of C and N confirm their changes associated with canonical extra mixing proposed by Denissenkov & Pinsonneault (2008). The Na-O correlation is open to question unlike the Na-Si correlation which is likely to exist. The Al-Mg and Al-Na correlations are consistent with the data obtained for the field giants with [C/Fe] < –0.5 (Roederer et al., 2014). According to the distribution of elements depending on their atomic numbers in the atmosphere of HD 6268, it is a metal-poor main r-process enriched star.